Humane and sustainable smart cities : a personal roadmap to transform your city after the pandemic - Costa, Eduardo (Academic Press, 2021)
Humane and Sustainable Smart Cities explores how to develop emergent smart cities that are rooted in humane, innovative and sustainable values (CHIS). The book considers the move from technocratic and idealized smart metropole to humane cities as a product of fundamental demographic changes, the development of a usage-based rather than an ownership economy, the novel implications of digitalization, decentralization and decarbonization, and Internet-enabled changes in public opinion towards democratization and participation. The book's authors explore seven dimensions and characteristics of humane, sustainable and innovative cities in the developing world: the economy, people, the place, energy and the environment, mobility, social inclusion and governance. Additional sections the operationalization of the CHIS concept into formal planning, policy implementation, and impact assessment considerations. Final discussions center on building a roadmap for planners seeking to design development policies conducive to human values and long-term social viability.